LPA1, LPA2, LPA4, and LPA6 receptor expression during mouse brain development. Issue 5 (27th March 2019) - Suckau, Olga; Gross, Isabel; Schrötter, Sandra; Yang, Fan; Luo, Jiankai; Wree, Andreas; Chun, Jerold; Baska, David; Baumgart, Jan; Kano, Kuniyuki; Aoki, Junken; Bräuer, Anja U.
Abstract: Background: LPA is a small bioactive phospholipid that acts as an extracellular signaling molecule and is involved in cellular processes, including cell proliferation, migration, and differentiation. LPA acts by binding and activating at least six known G protein–coupled receptors: LPA1–6 . In recent years, LPA has been suggested to play an important role both in normal neuronal development and under pathological conditions in the nervous system. Results: We show the expression pattern of LPA receptors during mouse brain development by using qRT‐PCR, in situ hybridization, and immunocytochemistry. Only LPA 1, LPA 2, LPA 4, and LPA 6 mRNA transcripts were detected throughout development stages from embryonic day 16 until postnatal day 30 of hippocampus, neocortex, cerebellum, and bulbus olfactorius in our experiments, while expression of LPA 3 and LPA 5 genes was below detection level. In addition to our qRT‐PCR results, we also analyzed the cellular protein expression of endogenous LPA receptors, with focus on LPA1 and LPA2 within postnatal brain slices and primary neuron differentiation with and without cytoskeleton stabilization and destabilization. Conclusions: The expression of LPA receptors changes depends on the developmental stage in mouse brain and in cultured hippocampal primary neurons. Interestingly, we found that commercially available antibodies for LPA receptors are largely unspecific. Key Findings: LPA1, ‐2, ‐4, and ‐6 genes are dynamically expressed during postnatal brain development. LPA1, ‐2, ‐4, and ‐6 genes are differently expressed in the hippocampus, neocortex, cerebellum, and bulbus olfactorius. LPA1 and ‐2 gene expression alters during neuronal differentiation. LPA1, ‐2, ‐3, ‐4, and ‐6 genes are expressed in glia cells, but differed in gene expression levels.